Où va le temps de travail ? - Rozenblatt, Patrick (Relations industrielles / Industrial Relations, 2002)
The article reviews the book, "Où va le temps de travail ?, edited by Gilbert de Terssac and Diane-Gabrielle Tremblay.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; Labor unions; SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z; Working hours